The financial performance determinants of the largest banks in Kazakhstan - Yespergenova, L.; Zhakusheva, Zh.; Faizulayev, A. (The Journal of Economic Research & Business Administration, 2023)
The banking industry plays a significant role in the development of the economic growth of the country. The purpose of this study is to determine the key factors that influence the profitability of the banking industry in Kazakhstan from 2012 to 2020 using firm-specific and macroeconomic variables.
Keywords: profitability; largest banks; economic growth; political stability